Was Levinas an Antiphilosopher? Archi-ethics and the Jewish Experience of the Prisoner - Matthew R. McLennan; Deniz Guvenc (Journal of French and Francophone Philosophy, 2015)
This paper explores Levinas’s Carnets de captivité and Écrits sur la captivité in light of Badiou’s category of ‘antiphilosophy’. We make four movements: firstly, a description of what antiphilosophy is; secondly, an explanation of why the category of antiphilosophy is important to a reading of Levinas; thirdly, an exposition of the antiphilosophical elements of the Carnets and Écrits on captivity; and fourthly, we situate our reading of the notebooks within the larger context of Levinas’s post-captivity work.